Answer:
g(x) = -12x + 48
Explanation:
Given function:
![f(x)=-3x](https://img.qammunity.org/2023/formulas/mathematics/college/ng8qg1yxbunyhbi5xa77hxecw6ss0k413i.png)
To transform a function by a vertical stretch of 4 units, multiply the function by the scale factor.
To translate a function to the right by 4 units, subtract 4 from the x-value of the function.
Therefore, the equation for g(x) is:
![\begin{aligned}\implies g(x)&=4f(x-4)\\&=4 \cdot -3(x-4)\\&=-12(x-4)\\&=-12x+48\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/iynut80bkimxq3ob9v8ac8g14rm9uo562t.png)